Car-use reduction in 15-Minute Cities. A matter of modal shift or shorter travel distances? - Marta-Beatriz Fernández Núñez; Monika Maciejewska; Laia Mojica; Oriol Marquet (Journal of Urban Mobility)
Policies such as the 15 Minute City seek to reduce car use by ensuring the spatial concentration and proximity of everyday activities. This paper examines how proximity to nearby services in Barcelona affects car use and analyzes whether proximity to everyday destinations affects modal choice and car trip durations differently. By matching self-reported travel behavior data and a series of GIS-based minimum walking travel times to 25 distinct everyday destinations, we are able to assess the links between proximity availability and actual car use. Our findings indicate that closer everyday destinations influence car usage by reducing the frequency of car-based modal choices, though they do not alter travel distances for those who continue to use cars. This study contributes to evidencing the effect of the 15 Minute City's premise regarding car usage reduction.